Analysis of hepatitis B virus genotypes by restriction fragment length polymorphism (2016)
ABSTRACT: Introduction: Ten viral genotypes (A-J) distributed in all continents have been described for hepatitis B virus (HBV). One of the methodologies for determining the viral genotype is the restriction fragment length polymorphism (RFLP) technique, a simple and relatively inexpensive method, albeit with some limitations. Objective: The initial objective of the project was to identify the HBV genotypes by RFLP in serum samples obtained from patients and blood donors. However, due to the discrepancies of RFLP patterns it was also necessary to perform phylogenetic genotyping and in silico analysis of HBV sequences. Materials and methods: We obtained 56 serum samples. DNA extraction was followed by PCR amplification of a fragment of HBV ORF S. We analyzed PCR products by RFLP with AlwI, BsrI, CfrI, HpaII and StyI, and we sequenced some. We compared the patterns obtained with those in previous reports. We also performed RFLP analysis in silico since we found differences between the patterns expected and those obtained Results: We identified genotypes A and F, subgenotype F3, in the samples. This result is in agreement with those of previous studies carried out in Colombia; indeed, subgenotype F3 is the most frequent in the Andean region of the country, while genotype A is the most frequent HBV genotype in the western region (department of Chocó). Based on the in silico analysis of 229 HBV sequences from GenBank and 11 sequences of this study, we identified the RLFP pattern for genotype F, subgenotype F3, and we described some modifications of genotype A RFLP patterns. Conclusions: We identified the single nucleotide polymorphism pattern for genotype F, subgenotype F3, by in silico analysis and sequencing. Further robust in silico analyses are necessary to validate the RFLP patterns of HBV genotype and subgenotypes.